2020
DOI: 10.1111/are.14606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing full‐fat soya beans and fish trim for sustainable sablefishAnoplopoma fimbriafeeds

Abstract: To quantify the efficacy and cost of different soya protein ingredients, heated soya beans (HSB) and underprocessed (SB) full-fat soya beans (FFSB), soya protein concentrate (SPC) and trim waste from Pacific whiting (Merluccius productus) were incorporated into feeds for the cold water marine sablefish (Anoplopoma fimbria). Feed ingredients for this study were processed using an experimental heated ball mill with demonstrated potential as an affordable process for rural or small-scale feed production. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The fish used in this study received a commercial diet at 1% of their body weight distributed over at least two feeding events per day. Recent studies recommend feeding sablefish to satiation once every other day to allow for adequate feed conversion and consistent intake of the feed [ 42 , 43 ]. Reduced feed intake has been observed after four days of daily feeding, attributed to a prolonged gastrointestinal passage in this species [ 42 ] (and personal communication with Ron Johnson).…”
Section: Discussionmentioning
confidence: 99%
“…The fish used in this study received a commercial diet at 1% of their body weight distributed over at least two feeding events per day. Recent studies recommend feeding sablefish to satiation once every other day to allow for adequate feed conversion and consistent intake of the feed [ 42 , 43 ]. Reduced feed intake has been observed after four days of daily feeding, attributed to a prolonged gastrointestinal passage in this species [ 42 ] (and personal communication with Ron Johnson).…”
Section: Discussionmentioning
confidence: 99%
“…The fish used in this study received a commercial diet at 1% of their body weight distributed over at least two feeding events per day. Recent studies recommend feeding sablefish to satiation once every other day to allow for adequate feed conversion and consistent intake of the feed (37,38). Reduced feed intake has been observed after four days of daily feeding, attributed to a prolonged gastrointestinal passage in this species (37) (and personal communication with Ron Johnson).…”
Section: Discussionmentioning
confidence: 99%
“…in alternative feeds for sablefish. Using heated ball mill processing, Nicklason et al (2020) found sablefish readily accept and grow well on a diet containing approximately 20% full fat soybeans after processing with wet heat.…”
Section: Current Alternative Feeds Research With Sablefishmentioning
confidence: 99%
“…Results indicate that properly processed full fat soybeans perform as well as more expensive soybean protein concentrates for this marine species and that sablefish may be tolerant to some anti-nutritional biomolecules (e.g., oligosaccharides and saponins) found in full fat soybeans that reduce feed performance in other cultured species, such as Atlantic salmon. An economic analysis of feed costs revealed coprocessing of fish trim with full fat soybeans shows great potential as an affordable process for rural or small-scale feed production for sablefish (Nicklason et al, 2020).…”
Section: Current Alternative Feeds Research With Sablefishmentioning
confidence: 99%